2020
DOI: 10.1080/14616696.2020.1828975
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country differences in anxiety and behavioral response to the Covid-19 pandemic

Abstract: The Covid-19 pandemic is affecting health, social, mental, and economic wellbeing worldwide, and taking precautions and cooperation is crucial at the individual level. Using data from various sources, this study examines crosscountry differences in anxiety levels and behavioral responses to the Covid-19 pandemic. Specifically, I investigate how economic preferences and development at the country-level are associated with anxiety and behavioral response and whether these factors explain contextual differences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…This is in agreement with the finding that individual anxiety and behavioral responses were stronger in societies characterized by greater altruism, patience (in other words, time preferences for long-term orientation), and development measured via three components of the Human Development Index such as the standard of living, education, and health (Buyukkececi 2020). Stronger individual health-protective behavioral responses were associated with positive reciprocity and trust at the country level, which seems to be related to social norms (Buyukkececi 2020). Using an organizational perspective, Teekens et al (2020) showed how social resilience can also be understood as resulting from specific workgroup characteristics and individual motivations that buffer against external shocks.…”
Section: Psychological Aspectswell-being and Resilience Vs Stress Ansupporting
confidence: 90%
See 4 more Smart Citations
“…This is in agreement with the finding that individual anxiety and behavioral responses were stronger in societies characterized by greater altruism, patience (in other words, time preferences for long-term orientation), and development measured via three components of the Human Development Index such as the standard of living, education, and health (Buyukkececi 2020). Stronger individual health-protective behavioral responses were associated with positive reciprocity and trust at the country level, which seems to be related to social norms (Buyukkececi 2020). Using an organizational perspective, Teekens et al (2020) showed how social resilience can also be understood as resulting from specific workgroup characteristics and individual motivations that buffer against external shocks.…”
Section: Psychological Aspectswell-being and Resilience Vs Stress Ansupporting
confidence: 90%
“…Further studies indicate the importance of the context in which individuals operate. Risk perceptions appeared to be lower among countries with stronger welfare states, but only if countries did not introduce preventive measures (Buyukkececi 2020). This is in agreement with the finding that individual anxiety and behavioral responses were stronger in societies characterized by greater altruism, patience (in other words, time preferences for long-term orientation), and development measured via three components of the Human Development Index such as the standard of living, education, and health (Buyukkececi 2020).…”
Section: Psychological Aspectswell-being and Resilience Vs Stress Ansupporting
confidence: 79%
See 3 more Smart Citations